Hubungan Mutu Pelayanan Dengan Kepuasan Pasien Rawat Jalan Pada Poli KIA Di Puskesmas Gunung Sindur Tahun 2020 - Ersarani Aldrina Ramadhanty (2021)
Background : the maternal mortality rate (MMR) in 2015 was still 305 / 100,000 live births. And the infant mortality rate (IMR) was 32 / 1,000 live births in 2015. According to 2019 health profile data, Low Birth Weight (LBW) is the highest cause of infant mortality aged 0-28 days in Indonesia, amounting to 35.3%. Puskesmas Gunung Sindur had a very high number of LBW babies at Gunung Sindur Puskesmas, which is 160 LBW babies (8.95%). This study aims to determine the correlation between service quality and patient satisfaction at the ANC service. Method : This research used quantitative method with cross-sectional approach. It was conducted in January 2021 with a total sample of 172 people. The sampling technique was accidental sampling. This research use chi square statistical tests and collected the data by using kuesioner. Result : This research showed that there were a correlation between service quality based on the dimensions of tangible, reliability, responsiveness, assurance, and empathy with antenatal care (ANC) patient statisfaction (p-value = 0.000). Conclution : The suggestions for health centers are to improve the service quality for the ANC service so it will make the mother and child health be better. Keyword : Service Quality, Patient Statisfaction, ANC